Preoperative augmentative and alternative communication enhancement in pediatric tracheostomy. (5th September 2019) - Santiago, Rachel; Howard, Michelle; Dombrowski, Natasha D.; Watters, Karen; Volk, Mark S.; Nuss, Roger; Costello, John M.; Rahbar, Reza
Abstract : Objectives/Hypothesis: Describe augmentative communication tools and strategies used by pediatric patients referred to inpatient speech‐language pathologists prior to tracheostomy placement. Study Design: Retrospective review. Methods: A review of patients who underwent initial tracheostomy placement from 2013‐2016 was conducted at a tertiary pediatric center. Eligible patients were those who were referred to a specialized speech‐language pathologist prior to the date of the tracheostomy placement to support communication abilities. Patients were identified by surgical procedural and billing codes. Data collected included patient demographics, speech and language disorders, and interventions performed. Chart review and cross analysis of billing data for types of assessment and intervention procedures were conducted by two speech‐language pathologists for consensus agreement. Results: Forty‐six patients (aged 1 month–27 years, mean = 12.9 years) were included in the study. Average time between the bedside communication assessment and tracheostomy procedure date was 17 days. Baseline speech‐language disorders were identified in 11 patients (24%). Thirty‐eight (83%) patients were nonspeaking at the time of consultation. Thirty‐two (70%) patients utilized an electronic communication tool, and 36 (78%) utilized low‐technology communication strategies during the preoperative period. A total of 32 (70%) patients were documented as using no‐technology or speech‐enhancement strategies during the acute hospitalization. Conclusions: Multidisciplinary tracheostomy teams should consider consultation to speech‐language pathologists for patients prior to tracheostomy placement to assess for utility of high‐technology, low‐technology, and no‐technology augmentative and alternative communication strategies. Level of Evidence: 4 Laryngoscope, 130:1817–1822, 2020